The Brawner Rule—Why? or No More Nonsense on Non Sense in the Criminal Law, Please! - Joseph Goldstein (Washington University Law Quarterly, 1973)
This Article will focus primarily on two matters in the Brawner court's opinion: 1) its decision not to abolish the insanity defense; and 2) its decision to permit the introduction of evidence concerning a defendant’s abnormal mental condition if relevant to establishing or negating the specific intent element of certain crimes.
Keywords: Brawner v. United States; 417 F.2d 969 (1972)